Education, experienced harm from others' drinking and personal alcohol consumption. (30th September 2020) - Berg-Beckhoff, G; Stock, C; Bloomfield, K
Abstract: Background: Risky alcohol consumption is associated not only with harm to the drinker, but also to those in the drinker's environment. Recent research has begun to examine the extent of such harm from others' drinking. In this study, we examined whether education functions as an effect modifier on the association between experienced harm from others' drinking (EHFOD) and risky alcohol use. Methods: Data from the 2011 Danish national alcohol and drug survey (n = 5133) were linked with data from Statistics Denmark. Survey response rate was 64%. Data on various alcohol use indicators were collected via internet questionnaires or telephone interviews. EHFOD was based on 8 indicators of harm from drunken people (e.g. being insulted, property damaged, being physically harmed). We grouped EHFOD into hassles, harassment or harm/damage. Multiple logistic regression was used to examine the association between EHFOD and own drinking behavior, stratified by sex and education. Covariates included age, employment status, rural residence, income and civil status. Results: One-year prevalence of EHFOD was 50%. We found a positive and significant relationship between own alcohol consumption and harassment as well as harm/damage. Effect modification of education was significant for harassment. Odds ratios for risky drinking behavior and harassment was 5.50 (95%CI: 3.49-8.65) in low educational group among men, and 1.42 (95%CI: 0.98-2.07) in the high educational group among men. Conclusions: Our study confirms an overall positive relationship between EHFOD and drinking behavior but varies by type of EHFOD. Furthermore, education modified this effect, but only for harassment. More research is necessary to better understand how drinking patterns diverge between low and high educational groups, and how this differentially affects risk for alcohol-related harms including the experience of harm from others' drinking. Key messages: One-year prevalence of experienced harm from others' drinking is high (50%) in Denmark. There is positive relationship between EHFOD and drinking behavior but it varies by type of EHFOD; education is an effect modifier.